Performance, Macro Economic Factors, and Company Characteristics in Indonesia Consumer Goods Company - Bambang Sucipto; *Muhammad Yusuf; Yuyun Mulyati (Universitas Syiah Kuala, 2022)
It and internal company conditions strongly influence company performance in the consumer sector. This study examines how macroeconomic and company characteristics affect corporate financial performance in consumer goods companies. This study's population now seems to be goods sector companies listed on the Indonesia Stock Exchange. The results of the systematic sampling technique and data analysis methods using several regression analyses confirmed that macroeconomic factors had no significant effect on company performance. Significant company. The characteristic is the level of corporate debt. The level of debt leverage has a negative and significant impact on company performance, indicating that the higher the company's debt, the reduced the company's performance. The sample size of this study is confined to consumer goods companies, so it cannot be generalized to other business sectors.